Design of an end effector for a manipulator with loading and unloading mechanisms - Chan, Yi Han (2022)
The industrial manipulator is competent to lift and manipulate heavy loads. It utilizes a cylinder to supply pressure to the manipulator's arm for the loading and unloading mechanism. To achieve this objective, the conventional type of industrial manipulator often requires the operator to manually press the push buttons for pressure adjustment. However, this is extremely tedious and timeconsuming. Therefore, the purpose of the research is to design a semi-automatic load balancing system for the manipulator and end effector control system. An operator control centre was also designed to be installed on the end effector to ease load manipulation. Throughout the research, PLC programming was introduced to transform solely pneumatic control systems into electropneumatic control systems. FluidSIM software was used to build and simulate the pneumatic control system for the manipulator and end effector. The manipulator cylinder force at different angles of tilt was analysed to compute the pressure required for the manipulator's arm during load manipulation. From the result, the manipulator semi-automatic load balancing system is capable to work at no-load, loaded, loading up, and down operations. Its design was evolved in four stages to add in loading up regulator, safety features, and implement PLC programming. The final design comprises three pressure regulators, and they are no-load, loaded, and loading up regulators which work at operating pressures of 0.3 MPa, 0.658 MPa, and 0.417 MPa respectively. The percentage difference between theoretical and actual cylinder supply pressure decreases from 29.5% to 5.15% after the design improvement. In addition, there were three safety features including halting operation and methods to cater to loss of load and supply pressures were implemented. Furthermore, the end effector electro-pneumatic control system resulted in correct cylinder piston rod movements for clamp levering, fork opening, and closing operations. Lastly, the operator control centre was designed according to human anthropometric limitations and contributed to the maximum vertical lift of 1274 mm. In conclusion, the manipulator and end effector control systems are proven to be feasible and functioned well. This is due to the small percentage difference in supply pressure and correct piston rod movements. The operator control centre was successfully tested in aiding loading and unloading mechanisms. In short, all objectives of the project were attained.